Mapping memory : visuality, affect, and embodied politics in the Americas - Murphy, Kaitlin M. (Fordham scholarship online., 2019)
In 'Mapping Memory', Kaitlin M. Murphy analyzes a range of visual memory practices that have emerged in opposition to political discourses and visual economies that suppress certain subjects and overlook past and present human rights abuses. From the Southern Cone to Central America and the US-Mexico borderlands, and across documentary film, photography, performance, memory sites, and new media, she compares how these visual texts use memory as a form of contemporary intervention.